Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) sebagai Sumber Pendapatan Asli Daerah dalam Menunjang Pembangunan Daerah di Indonesia - Anita Sri Wulandari; Rudi Sanjaya; Melpha Therecia Nainggolan; Mohammad Galih Arya C (Pajak dan Manajemen Keuangan, 2026)
This study aims to analyze the role of the Land and Building Tax (BPHTB) as a source of Regional Original Revenue (PAD), identify various challenges faced in the collection process, and examine strategies for optimizing BPHTB management to support sustainable regional development. The research method used is qualitative research with a descriptive approach through literature review. Data were obtained from various secondary sources, including laws and regulations, books, scientific journals, government reports, and relevant previous research results. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that BPHTB makes a significant contribution to Regional Original Revenue (PAD), especially in regions with high levels of property transaction activity. In addition to functioning as a source of regional revenue, BPHTB also plays a role in supporting orderly land administration and legal certainty over asset ownership. However, optimizing BPHTB revenue still faces various obstacles, such as low taxpayer compliance, reporting transaction values that do not match actual conditions, limited data integration between agencies, and suboptimal use of information technology. Therefore, efforts are needed to increase tax socialization, digitize services, strengthen inter-agency coordination, and improve the competence of apparatus to improve the effectiveness of BPHTB management. With optimal management, the Land and Building Acquisition Tax (BPHTB) can be an effective instrument in strengthening regional fiscal capacity and supporting sustainable regional development.